2016
DOI: 10.1007/s10897-016-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of a Genetic Counseling Peer Supervision Group

Abstract: Supervision is a practice that is utilized by a variety of practitioners to hone their counseling skills. Genetic counselors have embraced the supervision process, and some seek out supervision in a group setting with peers. Researchers have described the structure and content of genetic counseling peer supervision groups, and provided evidence for the benefits of seeking peer supervision. This study aimed to describe the interpersonal aspects of one genetic counseling peer supervision group, including persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…56 Studies also reported a lack of quality in supervision when supervisors were unfamiliar with professional guidelines (ie, standards set by regulators), their role and responsibilities as a supervisor, ethical standards set in place by employers and inadequate educational preparation. 11 Lack of supervisor competence and skills was identified in a number of studies highlighting barriers to effective clinical supervision, such as: being intolerant, blameful and inflexible, 2 being unable to deal with unmotivated supervisees 76 87 and manage differing personality types, 108 the lack of ability to share feelings, 49 inability to give appropriate feedback 51 and an inability to understand personal issues. 35 Lack of understanding and support when dealing with underperformance Supervision should facilitate learning opportunities when needed.…”
Section: Lack Of Supervisor Training and Supportmentioning
confidence: 99%
“…56 Studies also reported a lack of quality in supervision when supervisors were unfamiliar with professional guidelines (ie, standards set by regulators), their role and responsibilities as a supervisor, ethical standards set in place by employers and inadequate educational preparation. 11 Lack of supervisor competence and skills was identified in a number of studies highlighting barriers to effective clinical supervision, such as: being intolerant, blameful and inflexible, 2 being unable to deal with unmotivated supervisees 76 87 and manage differing personality types, 108 the lack of ability to share feelings, 49 inability to give appropriate feedback 51 and an inability to understand personal issues. 35 Lack of understanding and support when dealing with underperformance Supervision should facilitate learning opportunities when needed.…”
Section: Lack Of Supervisor Training and Supportmentioning
confidence: 99%
“…As for supervision, there are no requirements directly related to the genetic counselor's qualifications and efforts to obtain supervision depend on each individual and each workplace. Previous studies have reported the value of supervision and peer supervision to developing genetic counseling skills; however, difficulties in expanding supervision have also been reported (Atzinger et al, 2014; Berg et al, 2018; Lewis et al, 2017). As many genetic counselors in Japan also have difficulty obtaining appropriate supervision, new systems for self‐improvement will need to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to collaborating with other healthcare professionals, it is important for countries with the developmental stage of the however, difficulties in expanding supervision have also been reported (Atzinger et al, 2014;Berg et al, 2018;Lewis et al, 2017).…”
Section: Challenges To Establishing and Developing Genetic Counselimentioning
confidence: 99%
“…We utilized practitioner‐based enquiry (PBE) for this work, a ‘process in which teachers, tutors, lecturers and other education professionals systematically reflect on their own institutional practices’ (Murray, 1992 ). Practitioner‐centered research techniques have been previously reported in the genetic counseling literature (Lewis et al., 2017 ; Middleton et al., 2007 ) and found to generate unique insight.…”
Section: Methodsmentioning
confidence: 99%